Comparisons of cardioprotective efficacy between fibroblast growth factor 21 and dipeptidyl peptidase-4 inhibitor in prediabetic rats - Tanajak P. (2017)
© 2017 John Wiley & Sons Ltd Aims: Comparative efficacy between fibroblast growth factor 21 (FGF21) and vildagliptin on metabolic regulation, cardiac mitochondrial function, heart rate variability (HRV), and left ventricular (LV) function is not known. We hypothesized that FGF21 and vildagliptin share a similar efficacy in improving these parameters in high fat diet (HFD)-induced obese-insulin resistant rats. Methods: Twenty-four male Wistar rats were fed with either a normal diet (ND) or a HFD for 12 weeks. Then, ND rats were received vehicle (NDV). Rats in the HFD group were divided into three subgroups to receive either vehicle (HFV), recombinant human FGF21 (rhFGF21, 0.1 mg/kg/d, ip; HFF), or vildagliptin (3 mg/kg/d, PO; HFVil) for 28 days. Results: HFV rats developed obese-insulin resistance, increased serum tumor necrosis factors alpha (TNF-α) level, impaired heart rate variability (HRV) together with cardiac mitochondrial dysfunction, and LV dysfunction. Cardiac apoptosis was markedly increased in HFV rats indicated by decreased B-cell lymphoma 2 (Bcl-2) with increased Bcl2-associated X-protein (Bax) and cleaved caspase 3 expression. Cardiac FGF21 signaling pathways were markedly decreased in HFV rats indicated by decreased phosphor-fibroblast growth factor receptors 1 (p-FGFR1), phosphor-extracellular signal-regulated protein kinases 1 (p-ERK1/2), proliferator-activated receptor gamma coactivator 1-alpha (PGC-1α), and carnitine palmitoyltransferase-1 (CPT-1) expression. Although both FGF21 and vildagliptin similarly attenuated these impairments, only HFF rats had decreased body weight, visceral fat, and serum TNF-α levels. Conclusions: FGF21 exerts better metabolic regulation and inflammation reduction than vildagliptin. However, FGF21 and vildagliptin shared a similar efficacy for cardioprotection by improving HRV and LV function.